Institutional Interconnectivity of Clove Agribusiness - Nur Azizah; Imam Mujahidin Fahmid; Muhammad Arsyad; Asthutiirundu Asthutiirundu; Yusmiati Sabang (International Journal of Education, Information Technology, and Others, 2020)
The development of clove agribusiness requires the support of an active role and cooperation between various parties who have different interests and influences. Clove management is inseparable from the involvement of all stakeholders (government, private and community). The still weak cross-sectoral coordination is an important issue in formulating development strategies in the 2016-2021 Tidore Islands Mid-Term Development Plan. Therefore it is necessary to have a study of the role of stakeholders in realizing the development of sustainable clove agribusiness. This study aims to identify and analyze stakeholders by mapping stakeholders based on their influence and interests, outlining the roles of each stakeholder in clove management. This research uses the case study method. Data collection techniques about the role of stakeholders using the snowball sampling method were obtained from the results of interviews with the help of a set of questions or questionnaires presented in a descriptive qualitative analysis. The results showed that there were 12 (twelve) stakeholders involved in the development of agribusiness including primary stakeholders, namely farmers and farmer groups, key stakeholders namely the Department of Agriculture, Agricultural Extension Center, Agricultural Extension agent, Collector Traders, Production Faciility traders, Regional General Corporation Mandiri, a secondary stakeholder, namely the Village Chief, Department of Industry, trade, cooperatives and small and medium businesses, Farmers Group Associations, and college nuku. In addition, the findings in this study are social networks that are formed, sentiment networks, namely social networks formed based on blood / family relationships, work networks are networks formed because of relationships based on work, and networks of interests are networks formed due to relationships of interest.